The COMT Val158Met polymorphism does not modulate the after‐effect of tDCS on working memory - Jongkees, Bryant J.; Loseva, Alexandra A.; Yavari, Fatemeh B.; Nitsche, Michael A.; Colzato, Lorenza S. (The European journal of neuroscience, 2019)
Transcranial direct current stimulation (tDCS) can alter cortical excitability, neural plasticity, and cognitive‐behavioral performance; however, its effects are known to vary across studies. A partial account of this variability relates to individual differences in dopamine function. Indeed, dopaminergic manipulations alter the physiological and cognitive‐behavioral effects of tDCS, and gene polymorphisms related to dopamine have predicted individual response to online tDCS (i.e., stimulation overlapping with the critical task). Notably, the role of individual differences in dopamine has not yet been properly assessed in the effect of offline tDCS (i.e., stimulation prior to the critical task). We investigated if and how the COMT Val158Met polymorphism (rs4680) modulates the after‐effect of prefrontal tDCS on verbal working memory (WM). One hundred and thirty‐nine participants were genotyped for the COMT Val158Met polymorphism and received anodal‐over‐left, cathodal‐over‐right (AL‐CR), cathodal‐over‐left, anodal‐over‐right (CL‐AR), or sham stimulation over the dorsolateral prefrontal cortex in a between‐subjects, pretest–posttest study design. WM was assessed using the N‐back task. The results provide no evidence that the COMT polymorphism impacts the after‐effect of prefrontal tDCS on WM. Taken together with previous findings on dopamine and tDCS interactions, the results of the present study suggest that (a) indirect markers of dopamine (such as COMT) are differently related to online and offline effects of tDCS, and (b) findings from studies involving pharmacological manipulation should be generalized with caution to findings of inter‐individual differences. In sum, we argue that state (i.e., a manipulation of) and trait (i.e., baseline) differences in dopamine may exert different effects on online and offline tDCS. Individual differences in dopamine activity may impact the effects that transcranial direct current stimulation (tDCS) over prefrontal cortex has on cognition. However, in the present study we found no evidence suggesting that the effect of offline tDCS, that is stimulation prior to the critical task, is modulated by differences in the COMT polymorphism, which influences prefrontal dopamine activity. Taken together with previous findings, this suggests that dopamine may differently impact tDCS overlapping with vs. prior to the critical task.